Penicillin-Induced Epileptiform Ecog Activity in Gerbils: Effects of Physical Exercise and a Diospyros Kaki Extract - Kayacan, Y.; Bahadir, A.; Cetinkaya, A.; Orallar, H.; Cakir, S.; Beyazcicek, E.; Onal, A.C.; Yildirim, A. (Нейрофизиология, 2016)
Mongolian gerbils (28 males) were divided into four groups, control (C), treadmill-exercised
(Ex), treated with the extract of Diospyros kaki (Dk), and treated with the Dk extract plus
exercised (Ex+Dk) groups. Animals of the respective groups were running-exercised for
30 min per day during 8 weeks, and the Dk extract (dose 20mg/kg) was given by gavage
during five days per week within the same period. After the treatment and exercise period,
an epilepsy model was produced by penicillin G injection (500 IU) into the left somatomotor
cortex, and electrocorticogram (ECoG) was recorded during 120 min. The mean frequency of
spike/wave complexes was significantly smaller in the Ex and Ex+Dk groups from the 65th
min of the observation period and, in the Dk group, from the 75th min than the respective
value in the C group (P < 0.01, P < 0.05, and P < 0.01, respectively). The differences in the
amplitude values and latency to onset of the spike/wave events among all groups usally did
not reach the significance level (P > 0.05), but, visin late stages of the observation period,
an antiseisure effect of the Dk extract was obvious. Thus, both the running exercise and
Dk extract applications inhibit penicillin-induced epileptiform activity by altering the spike/
wave frequency or severity of seizures observed in ECoG recordings. Further studies are
needed to determine the effects of physical activity of different intensities and forms and to
analyze the active compounds in the Dk extract. Монгольські піщанки (28 самців) були поділені на
чотири групи – контрольну (C), піддану тренуванню
на тредбані (Ex), групу з уведенням екстракту Diospyros kaki (східної хурми, група Dk) та групу з уведенням
вказаного екстракту, комбінованим із тренуванням
(Ex+Dk). Тварин відповідних груп тренували, примушуючи
бігати 30 хв на день протягом восьми тижнів; екстракт
Dk (20 мг/кг) уводився перорально п’ять днів на тиждень
протягом того самого періоду. Після періоду тренування
та введення екстракту у щурів індукували модельну
епілепсію за допомогою ін’єкції 500 МО пеніциліну G у
ліву соматомоторну кору і відводили електрокортикограму
(ЕКоГ) протягом 20 хв. У групах Ex та Ex+Dk середня
частота виникнення комплексів пік/хвиля була вірогідно
меншою, ніж у контролі, починаючи з 65-ї хв періоду
спостереження; те саме відмічалося в групі Dk починаючи
з 75-ї хв вказаного періоду (P < 0.01, P < 0.05 та P < 0.01
відповідно). Відмінності значень амплітуди ЕКоГ та
латентного періоду до появи комплексів пік/хвиля в усіх
групах звичайно не досягали рівня вірогідності (P > 0.05),
але на пізній ділянці періоду спостереження антисудомний
вплив екстракту Dk був очевидним. Отже, тренування бігом
та уведення екстракту хурми східної пригнічує індуковану
пеніциліном епілептиформну активність, змінюючи частоту
комплексів пік/хвиля та інтенсивність судомної активності,
що спостерігається в ЕКоГ. Потрібні подальші дослідження
для того, щоб визначити ефекти фізичної активності
різної інтенсивності та форми та проаналізувати активні
компоненти екстракту хурми.